CSC729: Advanced Multimedia Computing / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (Universiti Teknologi MARA (UiTM), 2018)
This course prepares students with the underlying fundamentals of multimedia elements to build advanced multimedia computing applications comprising of images, videos, and audio. The course covers the important multimedia computing methods starting with digital data representation as well as examining the spatial and temporal data. This course will also discuss the data compression techniques which are important to make modern, portable and networked multimedia possible. Finally, it will also include the discussion on multimedia data retrieval and the multimedia networked technologies. By attending this course, the students will be exposed to the core techniques and emerging multimedia applications and will prepare them to formulate novel approaches for future multimedia computing applications.